The Effect of Modular Portable Clamp on Electrical Heat Traces for Wellhead Icing Prevention - Arya Dwi Candra; Pradini Rahalintar; Akba Gushari; Muhammad Aulia Fikri; Novlian Adonia Borolla; Zulfan Zulfan; Zainal Abidin (Jurnal POLIMESIN, 2023)
Gas wells have numerous safety devices installed at the wellhead, including pressure sensors with high-high (HH) and low-low (LL) parameter set points that can close the shut-down valve (SDV). A phenomenon of icing was discovered on the wellhead tube wings during open well X operations (after shut-in wells). This occurs when wells are shut down for longer than three days, such as during turnaround operations or emergency situations. The occurrence of ice blocks on the wellhead tube wings during wellbore startup disrupts gas flow to well X and has the potential to result in an annual loss of production opportunity (LPO) of $960 million. When there is a significant heat release phenomenon around the wing tube area, the absence of a heating facility around the wellhead area is one of the most important factors in this icing. To prevent icing and ice blockage, a portable, modular electric heat trace with clamp-on attachment is installed. Heat Trace cable is connected to a portable generator for power. This device is capable of converting electricity into heat up to 167 °F (75 °C). The heat generated by the instrument will mitigate the sudden release of heat when the gas begins to flow. Modular portable clamp-on heat tracing has been demonstrated to eliminate the possibility of icing at the wellhead due to a significant drop in temperature and maintain the gas field's production rate.